1996
DOI: 10.1002/pro.5560050403
|View full text |Cite
|
Sign up to set email alerts
|

Simulated annealing with restrained molecular dynamics using CONGEN: Energy refinement of the NMR solution structures of epidermal and type‐α transforming growth factors

Abstract: The new functionality of the program CONGEN (Bruccoleri RE, Karplus M, 1987, Biopolymers 26:137-168;Bassolino-Klimas D et al., 1996, Protein Sci5:593-603) has been applied for energy refinement of two previously determined solution NMR structures, murine epidermal growth factor (mEGF) and human type-a transforming growth factor (hTGFa). A summary of considerations used in converting experimental NMR data into distance constraints for CONGEN is presented. A general protocol for simulated annealing with restrai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 47 publications
2
41
0
Order By: Relevance
“…The current implementation of CONGEN also allows use of dihedral angle constraints and J constraints. Successful applications of the general SA protocol described here and the CONGEN computer program to structure determinations of peptides and proteins using real NMR data will be described in detail elsewhere (Newkirk et al, 1994;Jendeberg et al, 1996;Tejero et al, 1996). In addition, the ability to model ensembles of structures with the correct averaging of NOES and vicinal coupling constants has been added to CONGEN recently.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The current implementation of CONGEN also allows use of dihedral angle constraints and J constraints. Successful applications of the general SA protocol described here and the CONGEN computer program to structure determinations of peptides and proteins using real NMR data will be described in detail elsewhere (Newkirk et al, 1994;Jendeberg et al, 1996;Tejero et al, 1996). In addition, the ability to model ensembles of structures with the correct averaging of NOES and vicinal coupling constants has been added to CONGEN recently.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, all of the structures described in these benchmark tests are initiated from extended conformations with randomly assigned initial velocities. In related work using real NMR distance constraints (Tejero et al, 1996), CONGEN structures generated from extended starting conformations (with randomly assigned initial velocities) also exhibit fewer constraint violations and lower energies than structures generated using a hybrid DG/SA algorithm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Biological data from EGF and at least one EGF-like domain show that disulfide bond isomers have significant bioactivity and suggests that the EGF fold can accommodate alternate disulfidebonding patterns. The disulfide bonds in murine EGF were altered to seven different patterns and structures were calculated incorporating all the restraints from the highest resolution restraint set available (Tejero et al, 1996). Results showed that besides the native (1-3,2-4,5-6), two other disulfide-bonding patterns: (1-2,3-4,5-6) and (1-3,2-5,4-6) satisfied the restraints as well as the native.…”
mentioning
confidence: 99%